The Effect of Regulations, Budget Politics, Organizational Commitment, Human Resources Competency and Procurement of Goods and Services on Budget Absorption (Study on Siak Regency OPD) - Putri T., Nikita Aurelia; Nasir, Azwir; Rofika, Rofika (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
This study’s objectives are to prove and test the factors that influence budget absorption, namely regulations, budget politics, organizational commitment, human resources competency and procurement of goods and services. This research is a quantitative study where the primary data is collected directly using a questionnaire which is measured using Likert scale. The population of this study were 5 financial management employees of all Regional Apparatus Organizations (OPD) of Siak Regency, with 30 OPDs in total. The total sample of this study was 90 respondents with the sampling technique, namely purposive sampling, who were in accordance with the position of the head of the service, financial technical implementation officials and treasurer of OPD spending. Data analysis was performed using multiple linear regression which was processed with the help of the SPSS version 23 program. The results of this study indicate that regulations, budget politics, organizational commitment, human resources competency and procurement of goods and services have a significant effect on budget absorption.